METODE PEMBELAJARAN SIMULASI DAN DEMONTRASI DI LABORATORIUM DENGAN HASIL BELAJAR MATA KULIAH KEPERAWATAN KEGAWATDARURATAN DI AKADEMI KEPERAWATAN KESDAM I/BB MEDAN MEDAN - Pangaribuan, Resmi; Pratama, Muchti Yuda (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Emergency nursing care is a nursing process in managing patients or patients to get independent and multidisciplinary care (collaborative) so that the expected outcome criteria can be achieved. The learning process involves complex activities, not just the transfer of knowledge from educators to students textually. In each learning process, efforts must be made to be able to deliver students to the proposed competency, including the underlying values and attitudes. The design of this study is a correlation , The sampling technique is to use the Slovin formula, namely the number of samples taken from affordable populations in this study. The results of the research conducted statistically showed that the Students of Nursing Academy of Kesdam I/BB Medan knew that there were 30 female students (46.9%) in the simulation category. Student of Nursing Academy in Medan I/BB Medan know about the adequate method of demonstration learning method as many as 34 students (53.1%). Students of Nursing Academy of Kesdam I/BB Medan about the learning outcomes of emergency nursing care from the category C value of 35 female students (54.7%). It is expected that the Medan I/BB Middle School Nursing Academy will maintain and further improve laboratory facilities and infrastructure to support the achievement of female students in midwifery care at the Nursing Academy of Kesdam I/BB.